Chlorin e6 keratin nanoparticles for photodynamic anticancer therapy. Issue 40 (6th April 2016) - Aluigi, A.; Sotgiu, G.; Ferroni, C.; Duchi, S.; Lucarelli, E.; Martini, C.; Posati, T.; Guerrini, A.; Ballestri, M.; Corticelli, F.; Varchi, G.
Abstract : Chlorin e6-conjugated keratin nanoparticles were obtained and their effectiveness as carriers for cancer photodynamic therapy was demonstrated in vitro . Abstract : This work describes the preparation of keratin and chlorin e6-conjugated keratin nanoparticles, KNPs and KNPs@Ce6 respectively, by comparing self-assembling and desolvation methodologies. Nanoparticles were characterized in terms of yield, size, morphology, Ce6 loading ratio and ability to produce reactive oxygen species (ROS) upon irradiation with white light. Overall, both methods provided nanoparticles of comparable dimensions, morphology and Ce6 loading ratio. KNPs@Ce6 obtained by a self-assembling procedure were able to produce ROS in a concentration and irradiation-time dependent manner, while displaying compelling evidence of their photostability. In vitro internalization and photo-toxicity studies were performed on osteosarcoma (U2OS) and glioblastoma (U87) cells lines to assess the ability of KNPs@Ce6 nanoparticles to act as delivery systems for photodynamic therapy of cancer. Importantly, at all the Ce6 considered concentrations, e.g. 0.5, 2.5 and 5.0 μg mL −1, no dark toxicity was detected while the amount of Ce6 inside the cells, significantly increased when loaded onto KNPs. The irradiation of tumor cells loaded with KNPs@Ce6 resulted in a greater cell death percentage (approximately 90%) as compared to free Ce6 in both cell types and at all the considered concentrations, thus showing KNPs as effective and promising delivery vehicles for photodynamic therapy applications.